The Effect of Progressive Muscle Relaxation for Fatigue in a Patient with Tuberculosis and Pneumonia - Rahmania, Sina Sabila; Nugraha, Bambang Aditya; Sari, Eka Afrima (Journal of Nursing Care, 2026)
Fatigue is a common and persistent symptom in patients with tuberculosis (TB), particularly in recurrent cases and when accompanied by pneumonia. Increased systemic inflammation and reduced activity tolerance often lead to functional decline, while pharmacological treatment alone may not sufficiently address fatigue. Progressive muscle relaxation (PMR) is a non-pharmacological intervention that reduces muscle tension and stress, support physiological recovery. This study describes the effect of PMR to reduce fatigue in a patient with recurrent tuberculosis and pneumonia. This study is a case review involving a 65-year-old female patient diagnosed with pulmonary TB and pneumonia. PMR was administered over four consecutive days, with one session lasting 15–20 minutes per session. The sessions were conducted at varying times, including in the morning, afternoon, or before bedtime. Fatigue levels were measured after each session using the Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F) Scale. The patient showed improvement in vital signs, with blood pressure increasing from 108/65 mmHg to 116/61 mmHg, heart rate decreasing from 111 to 62 beats per minute, and the FACIT-F score improved from 12 (severe fatigue) to 36 (mild fatigue), indicating a reduction in fatigue severity. Functionally, the patient was able to walk to the bathroom independently and no longer experienced weakness or dyspnea post-activity. These findings indicate that PMR contributed to a reduction in the patient’s fatigue level. This intervention has potential as a supportive rehabilitative strategy, with adjustments in duration and frequency based on patient condition.